Looking Ahead in Games Research: Entry Points into a Pragmatic Field of Inquiry - Siitonen, Marko (2021)
This thematic issue presents a number of emerging scholarships into the study of digital gaming. The articles are based on a 2019 symposium on game studies hosted by the Digital Games Research section of ECREA. As the phenomena related to digital gaming keep on evolving and emerging, so must research keep up with the times and constantly challenge itself. Whether speaking about validating previously developed research methods, imagining totally new ones, or even challenging the whole philosophy of science on which research is being done, there is a constant need for reappraisal and introspection within games research. As a cultural medium that has become deeply embedded into the social fabric of the 2020s, digital gaming continues to excite and challenge academia. This thematic issue provides a collection of approaches to look into the future that addresses some of the challenges associated with game research.